2021
DOI: 10.3389/fncel.2021.785433
|View full text |Cite
|
Sign up to set email alerts
|

Inflamma-MicroRNAs in Alzheimer’s Disease: From Disease Pathogenesis to Therapeutic Potentials

Abstract: Alzheimer’s disease (AD) is the most common cause of senile dementia. Although AD research has made important breakthroughs, the pathogenesis of this disease remains unclear, and specific AD diagnostic biomarkers and therapeutic strategies are still lacking. Recent studies have demonstrated that neuroinflammation is involved in AD pathogenesis and is closely related to other health effects. MicroRNAs (miRNAs) are a class of endogenous short sequence non-coding RNAs that indirectly inhibit translation or direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 121 publications
(121 reference statements)
2
30
0
Order By: Relevance
“…In addition, miR-155 is involved in the gene regulation of astrocytes. Activation of these cells induces upregulation of miR-155, which, by inhibiting the mRNA of SOCS-1, determines the high production of pro-inflammatory cytokines [ 48 ].…”
Section: Mir-155mentioning
confidence: 99%
“…In addition, miR-155 is involved in the gene regulation of astrocytes. Activation of these cells induces upregulation of miR-155, which, by inhibiting the mRNA of SOCS-1, determines the high production of pro-inflammatory cytokines [ 48 ].…”
Section: Mir-155mentioning
confidence: 99%
“…MiRNAs have been investigated as potential biomarkers for AD diagnosis, prognosis, and therapeutic for their involvement in multiple brain signalling pathways (Zhao et al 2020). MiR-21 has been shown to regulate microglia/astrocytes activation and link to neuroin ammatory signalling (Liang and Wang 2021). Li et al (Li et al 2019) showed that miR-21-5p in neuronal exosomes was increased and inhibited neuronal autophagy by targeting RAB11A.…”
Section: Introductionmentioning
confidence: 99%
“…For at least ~25 years mRNA-sized synthetic oligonucleotides have been in use employing different mechanisms of action from steric hindrance to diminished or enhanced degradation by endogenous RNase H- or L-type exo- and endo-nucleases naturally abundant in the cellular environment (Lennox and Behlke, 2011 ; Evers et al, 2015 ; Grabowska-Pyrzewicz et al, 2021 ). Optimized biochemical modification strategies originally designed for large mRNAs (~2,000–5,000 nt) have aided in the strategic design and current use of miRNA-based therapeutics (Lima et al, 2018 ; Liang and Wang, 2021 ; Nguyen et al, 2021 ). Chemical modification of synthetic sncRNA oligonucleotides can instill nuclease resistance, increase binding affinity to mRNA 3'-UTR ‘seed sequence' regions and complexation with lipophilic molecules such as cholesterol or other lipids can aid in the cellular uptake and/or targeting by nucleases (Simonson and Das, 2015 ; Nguyen et al, 2021 ; Walgrave et al, 2021 ).…”
Section: The Modulation Of Microrna Stabilitymentioning
confidence: 99%
“…In AD, how these specific alterations in miRNA abundance, speciation and complexity impact disease initiation, propagation and severity and whether they are the result, cause or effect, along the trajectory of this heterogeneous and complex disease in most cases remains unclear (Colangelo et al, 2002 ; Lukiw, 2007 ; Herrera-Espejo et al, 2019 ; Kinoshita et al, 2021 ; Li and Cai, 2021 ; Liang et al, 2021 ; Pogue and Lukiw, 2021 ). Specific drug targeting issues and complications can be overcome by extensive experimentation involving testing with differentially stabilized miRNAs, antagomirs and related anti-ribonuclease strategies, the updating and constant refinement of miRNA-based therapeutic approaches and by novel miRNA and/or antagomir delivery protocols using TgAD models as a guide (Kinoshita et al, 2021 ; Liang and Wang, 2021 ; Liang et al, 2021 ; Nguyen et al, 2021 ; Zhang et al, 2021 ). The route of administration into the brain of chemically modified and/or stabilized miRNA species, such as via intranasal, intrathecal or direct intracerebroventricular infusion often enables the functional delivery of stabilized oligonucleotides in the absence of any delivery vehicle both in murine models and in humans (Mai et al, 2019 ; Nogimori et al, 2019 ; Silva et al, 2020 ; Maimon et al, 2021 ; Nguyen et al, 2021 ).…”
Section: Experimental and Therapeutic Applications Of Stabilized Micr...mentioning
confidence: 99%